Effect of sonic and ultrasonic activation on organic tissue dissolution from simulated grooves in root canals using sodium hypochlorite and EDTA. (3rd December 2016) - Conde, A. J.; Estevez, R.; Loroño, G.; Valencia de Pablo, Ó.; Rossi‐Fedele, G.; Cisneros, R.
Abstract: Aim: To compare soft‐tissue dissolution by sodium hypochlorite, with an EDTA intermediate rinse, with or without activation with passive ultrasonic activation (PUI) or sonic activation using the Endoactivator (EA) or Eddy tips (ED). Methodology: The root canals of eighty‐three human maxillary central incisors were chemo‐mechanically prepared and the teeth split. A standardized longitudinal intracanal groove was created in one of the root halves. Eighty‐three porcine palatal mucosa samples were collected, adapted to fit into the grooves and weighed. The re‐assembled specimens were randomly divided into four experimental groups ( n = 20), based on the final rinse: no activation; EA; PUI; ED, using 2.5% sodium hypochlorite, with an EDTA intermediate rinse. A control group ( n = 3) was irrigated with distilled water without activation. The solutions were delivered using a syringe and needle 2 mm from working length. Total irrigation time was 150 s, including 60 s of activation in the specific groups. The study was carried out at 36 ± 2 °C. The porcine palatal mucosa samples were weighed after completion of the assays. Student paired t ‐test and anova were used to assess the intra‐ and intergroup weight changes. The multiple comparisons were evaluated using Bonferroni correction (α = 0.05). Results: Weight loss occurred in all experimental groups. Irrigant activation resulted in greater weight loss when compared to the nonactivated group [vs. EA ( P = 0.001); vs. PUI ( P < 0.001); vs. ED ( P < 0.001)]. No significant differences were found amongst the different activation systems. Conclusions: Activation increased the tissue‐dissolving activity of irrigants from artificial grooves in root canals of maxillary central incisors.